2014
DOI: 10.1016/j.compositesb.2013.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of composite structure with in-plane isotropic negative Poisson’s ratio: Effects of materials properties and geometry features of inclusions

Abstract: A novel composite structure with isotropic negative Poisson's ratio has been presented in our previous paper [1]. However, the previous study has only focused on the effects of random inclusions. In this work, an extended numerical study on the effects of materials properties and geometry features of inclusions is conducted in order to better understand the deformation mechanism and mechanical properties of this kind of composites. Using finite element method, the overall negative Poisson's ratio effects and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In this section, Finite Element Method has been utilized for the evaluation of effective elastic properties of two-phase SMP composites filled with randomly distributed and oriented GNPs. The geometry of inclusions plays an important role on the overall effective mechanical properties [29,30]. Thus, in this work we also study the effect of inclusion geometry in our finite element model where we change the aspect ratio of inclusions with platelet geometry.…”
Section: Three-dimensional Modeling and Numerical Considerationsmentioning
confidence: 99%
“…In this section, Finite Element Method has been utilized for the evaluation of effective elastic properties of two-phase SMP composites filled with randomly distributed and oriented GNPs. The geometry of inclusions plays an important role on the overall effective mechanical properties [29,30]. Thus, in this work we also study the effect of inclusion geometry in our finite element model where we change the aspect ratio of inclusions with platelet geometry.…”
Section: Three-dimensional Modeling and Numerical Considerationsmentioning
confidence: 99%
“…Currently, there are few auxetic materials showing isotropic behavior. These include disordered systems such as foams [5], randomly oriented composite laminates [23], granular materials [24] and composites with randomly distributed inclusions [25,26]. Alternatively, to achieve better control and tunability of the Poisson's ratio, ordered auxetic isotropic systems have been numerically designed, such as hexagonal chiral honeycombs [8,9], intricate networks of rods, hinges and springs [27], two-phase composite materials with hexagonal symmetry [28], assemblies of flexible frames and rigid cores [29] and systems of hard cyclic hexamers [30].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, plenty of reinforcements have been proposed or developed to fabricate auxetic composites, such as specific two-dimensional (2D) triangle inclusions [13,14,15], three-dimensional (3D) tetrahedron hollow shell [16,17], cellular honeycomb structure [18,19], double arrowhead [20,21], and chiral network [22]. Hou et al [14,15,16,17] found that the mechanical properties and deformation behavior of auxetic composites can be tailored by controlling the geometry features and the density of inclusions, and these findings were confirmed by Wang et al [6], Hu [13], and Li et al [18]. Recently, Bruggi et al theoretically investigated the synthesis of auxetic structures by a topology optimization approach for micropolar materials.…”
Section: Introductionmentioning
confidence: 99%